A case report of vanishing bile duct syndrome after exposure to pexidartinib (PLX3397) and paclitaxel - Piawah, Sorbarikor (NPJ Breast Cancer, 2019)
Pexidartinib (PLX3397) is a small molecule tyrosine kinase and colony-stimulating factor-1 inhibitor with FDA breakthrough therapy designation for tenosynovial giant-cell tumor, and currently under study in several other tumor types, including breast cancer, non-Hodgkin’s lymphoma, and glioblastoma. Here, we report a case of severe drug-induced liver injury requiring liver transplantation due to vanishing bile duct syndrome (VBDS) after exposure to pexidartinib in the I-SPY 2 Trial, a phase 2 multicenter randomized neoadjuvant chemotherapy trial in patients with Stage II–III breast cancer. We also review the current literature on this rare, idiosyncratic, and potentially life-threatening entity.